Hepatic cystic echinococcosis in Australia: an update on diagnosis and management. Issue 1 (11th October 2017) - Keong, Ben; Wilkie, Bruce; Sutherland, Tom; Fox, Adrian
Abstract : Background: Echinococcosis is an uncommonly encountered zoonotic disease caused by the taeniid Echinococcus . The only endemic species in Australia, Echinococcus granulosus, forms cysts in the liver in 70% of cases. The aim of this study was to review the literature to provide an evidence‐based narrative update on the diagnosis and management of hepatic cystic echinococcosis in Australia. Methods: We reviewed the literature, utilizing multiple research databases and citation tracking. Original research and review articles examining the diagnosis and management of hydatid disease in adults, published prior to 2016 and in the English language were included in our review. Results: Ultrasound is the gold‐standard screening test, whilst computed tomography has a role in emergency presentations and screening for multi‐organ involvement. Magnetic resonance imaging is the preferred second‐line imaging and better demonstrates biliary involvement. Medical therapy or PAIR (percutaneous aspiration, irrigation with scolicide and re‐aspiration) may be appropriate in selected cases; however, surgery remains the definitive treatment for active, large (>5 cm), symptomatic or complicated cysts. A variety of surgical techniques have been described, including conservative, radical and minimally invasive procedures. There is currently no consensus approach; surgical modality should be tailored to patient factors, relevant anatomy, local facilities and surgeons' expertise. Conclusion: Diagnosis and therapy in hepatic hydatid cysts have been significantly advanced by imaging, interventional radiology and surgical approaches in recent years. Surgery remains the mainstay of treatment for large, active, complicated or symptomatic hepatic hydatid cysts.